Cross-sectional association between hs-CRP/HDL-C ratio and physical frailty among middle-aged and older adults: findings from a population-based study - Wang, Yina; Su, Jing; Wang, Yang (Frontiers in Public Health, 2025)
BackgroundFrailty, characterized by functional decline and disability, is an emerging public health concern in aging populations. Chronic inflammation and low high-density lipoprotein cholesterol (HDL-C) levels are key contributors to the progression of frailty. This study aims to examine the association between the ratio of high-sensitivity C-reactive protein (hs-CRP) to HDL-C and frailty among middle-aged and older adults in the United States.MethodsOur study included participants aged 45 years and older from the 2015–2020 National Health and Nutrition Examination Survey (NHANES). Logistic regression and restricted cubic spline (RCS) analysis were utilized to assess the relationship between the hs-CRP/HDL-C ratio and frailty, adjusting for potential confounding covariates. Mediation analysis was performed to determine whether plasma proteins mediated this association. Least absolute shrinkage and selection operator (LASSO) regression was employed to identify variables strongly correlated with frailty, and a nomogram was subsequently developed based on these variables.ResultsOur study included 3,626 middle-aged and older participants, among whom 787(21.7%) were identified as frailty. After adjusting for all covariates, a high hs-CRP/HDL-C ratio was identified as a significant risk factor for frailty (OR = 1.736, 95% CI: 1.009–2.988). RCS analysis disclosed a nonlinear correlation between the hs-CRP/HDL-C ratio and frailty incidence. Furthermore, mediation analysis suggested that albumin and globulin partially mediated this association, accounting for 37.82% and 11.23% of the indirect effect, respectively. A nomogram, constructed using variables selected via LASSO regression, exhibited promising discriminative ability, with an area under the curve (AUC) of 79.7% (95% CI: 77.7–81.75%).ConclusionOur findings suggest that a higher hs-CRP/HDL-C ratio is associated with an increased risk of frailty among middle-aged and older adults. Albumin and globulin partially mediate this relationship. Additionally, the nomogram developed in our study shows strong predictive ability for identifying individuals at high risk of frailty in this population.